Pengaruh Struktur Modal, Kepemilikan Institusional dan Profitabilitas terhadap Nilai Perusahaan - Giawan Nur Fitria; Rista Bintara (Jurnal Akuntansi, Keuangan, Pajak dan Informasi (JAKPI), 2023)
This study aims to determine the effect of capital structure, institutional ownership, and profitability on firm value. This study used food and beverage manufacturing companies listed on the IDX with an observation period from 2017 to 2021. The purposive sampling method was used to determine the sample in this study. A total of 12 companies that meet the sample criteria, so there are 60 observational data. Data analysis techniques were performed using multiple linear regression analysis, and with the SPSS 23 program. Based on the test results, the capital structure and institutional ownership did not affect firm value, while profitability had a positive effect on firm value. This research contributes to further research which is an addition to the literature on firm value